The dynamics of near-surface prismatic loops in lead; AIP Conference Proceedings; Vol. 1698 : Advanced Materials in Technology and Construction, AMTC-2015 - Petelina Yu. Yulia; Samokhina S. Svetlana; Polosukhin K. Konstantin; Vik K. Kseniya; Petelin A. Alexander; Kolupaeva S. N. Svetlana Nikolaevna (2016, 2016)
Title screen